THE CELLULAR RIVERS OF LIFE: A COMPREHENSIVE REVIEW OF THE CORPUSCULAR ELEMENTS OF BLOOD - Asatullyev Rustam Baxtiyorovich; Kalandarova Marjona Turakulovna (TADQIQOTLAR, 2026)
Abstract: Blood, the liquid connective tissue that circulates throughout the human body, is composed of two main components: plasma (the liquid matrix) and formed elements (corpuscles). The corpuscular elements-erythrocytes (red blood cells), leukocytes (white blood cells), and thrombocytes (platelets)-perform essential functions that sustain life. Erythrocytes are responsible for oxygen transport, facilitated by the hemoglobin molecule; leukocytes constitute the cellular arm of the immune system, defending against pathogens and malignancies; and thrombocytes mediate hemostasis, preventing bleeding after vascular injury. This article provides a systematic review of the morphology, physiology, production (hematopoiesis), and clinical significance of each corpuscular element. Special attention is given to quantitative disorders (anemias, leukopenias, thrombocytopenias) and qualitative disorders (sickle cell disease, leukocyte adhesion deficiency, platelet function defects). The article also discusses laboratory assessment, including complete blood count, peripheral blood smear, and advanced flow cytometry. The review concludes with emerging therapeutic applications, including blood transfusion, hematopoietic stem cell transplantation, and platelet-rich plasma therapy.